Oblicz :

3(2x-3) =
4(x-2)-2(x+4) =
(x+1)(x-3)=
2x(x-1) =
4x (x-2)-2(x-1)=
3(x-1)+2(x-1)-(x-3) =
2x(x-y)-3(x-y)+2(xy-3) =
4x(x+y) -2y (x-y) + 2 (xy-3) =
-(x-1)-(x+2) + (x+3) =

Wymień Wyrazy Podobne :
2x , a , x2 , - a, -2x² , 0,5 x, 2a
Wkonaj Redukcję :
2x-3x-0,5_10x =
3x² + 5x² - 7x² - 10x² =
xy-2xy - 4xy +10xy =
x+y - 2x + 4y - 2x =


PROSZĘ O POMOC ;************ ! . ; ))
z Góryy Dzękuje ;) ;*

3

Odpowiedzi

2010-04-13T11:03:36+02:00
3(2x-3) =6x-9
4(x-2)-2(x+4) = 4x-8-2x-8=2x-16
(x+1)(x-3)=x*-3x+x-3=x*-2x-3 (*-kwadrat)
2x(x-1) = 2x*-2x
4x (x-2)-2(x-1)=4x*-8x-2x+2=4x*-10x+2
3(x-1)+2(x-1)-(x-3) = 3x-3+2x-2-x+3=4x-2
2x(x-y)-3(x-y)+2(xy-3) =2x*-2xy-3x+3y+2xy-6=2x*-3x+3y-6
4x(x+y) -2y (x-y) + 2 (xy-3) =4x*+4xy-4xy+2y*+2xy-6=4x*+2y*+2xy-6
-(x-1)-(x+2) + (x+3) = -x+1-x-2+x+3=-x+2

Wymień Wyrazy Podobne :
2x ,0,5x
a,- a,2a
x2 , -2x²
Wkonaj Redukcję :
2x-3x-0,5_10x =-11x-0,5
3x² + 5x² - 7x² - 10x² = -9x*
xy-2xy - 4xy +10xy = 5xy
x+y - 2x + 4y - 2x = -3x+5y

2010-04-13T11:03:39+02:00
6x-9
4x-8-2x-8=2x-16
x(do drugiej)-3
2x(do drugiej)-2x
4x(do drugiej)-8x-2x+2=4x(do drugiej)-10x+2
3x-3+2x-2-x+3=4x-2
2x(do drugiej)-2xy-3x+3y+2xy-6=2x(do drugiej)-3x+3y-6
4x(do drugiej)+4xy-2yx+2y(do drugiej)+2xy-6=4x(do drugiej)+4xy+2y-6
x(do drugiej)-2+x+3=x(do drugiej)+x+1


2010-04-13T11:04:23+02:00
1. 6x-9
2. 8x-8-2x-8=6x-16
3. x²-3x+x-3= x²-2x-3
4. 2x²-2x
5. 4x²-8x-2x+2=4x²-10x+2
6. 3x-3+2x-2-x+3= 4x-2
7. 2x²-2xy-3x+3y+2xy-6= 2x²-3x+3y-6
8. 4x²+4xy-2xy+2y²+2xy-6=4x²+4xy-6+2y²
9.-x+1-x-2 + x+3 = -x+2

1. 2x , a , x2 , - a, -2x² , 0,5 x, 2a = 2a,a,-a ; x2,2x,0,5x; -2x²

1. 2x-3x-0,5-10x = -11x-0,5
3x² + 5x² - 7x² - 10x² = -9x²
xy-2xy - 4xy +10xy = 5xy
x+y - 2x + 4y - 2x = -3x+5y